Implementation and evaluation of a quality improvement project: carepaths for Early Psychosis Intervention Programmes in Northeastern Ontario. Issue 6 (4th March 2016) - Bedard, Terry E.; Nadin, Shevaun; Zufelt, Cheryl; Cheng, Chiachen
Abstract: Aim: This study aims to describe the implementation and evaluation of a quality improvement project, which aimed to standardize services and documentation across several district Early Psychosis Intervention Programmes in a rural region of Canada (Northeastern Ontario). Method: A Carepath for early psychosis intervention (EPI), which outlined best practice EPI care pathways, was implemented across 12 EPI programme sites. It was hypothesized that the proportion of best practice interventions provided across the district programmes would increase after the implementation of the Carepath initiative and that documentation would be standardized. Pre‐Carepath and post‐Carepath chart audits evaluated the provision and documentation of EPI best practices that were specified in the Carepath. Results: Pre‐audits and post‐audits were completed on 110 and 108 client files, respectively. Chi‐squared tests revealed that the post‐audit frequencies were significantly higher than the pre‐audit frequencies for two of the 12 EPI best practices that were evaluated (i.e. assessed impact on family and assessment of substance use). Standardization of documentation did not improve significantly. Conclusions: The results are discussed in the context of barriers to implementing and evaluating the Carepaths. Various individual and agency level barriers are identified (e.g. staff resistance, resources and agency documentation parameters), and strategies to overcome them are discussed. It is concluded that, despite barriers to implementation and evaluation, Carepaths can be a useful tool for standardizing services and documentation across a network of EPI programmes and guiding programme evaluation and quality assurance.